Assessing the impact of deviations in optimized multistep flow synthesis on the scale-up - Sharma, M. K.; Raval, J.; Ahn, Gwang-Noh; Kim, Dong-Pyo; Kulkarni, A. (Reaction Chemistry & Engineering, 2020)
This manuscript highlights the unavoidable connection between manual and self-optimized flow synthesis protocols for multistep flow synthesis and its scale-up. While briefly summarizing the state of the art in the self-optimization approach, a brief summary of industrially scaled-up processes is also given. We have used as a case study the flow synthesis of ivacaftor that is optimized at the laboratory scale and is subjected to specific deviations deliberately. The resulting effects are captured in terms of their effect on the scale-up approach. The analysis shows that small deviations in performance viz. conversion or selectivity at every reaction step would lead to significant deviation in the process and the overall capital investment. Translating ``laboratory synthesis'' into ``commercial scale manufacturing'' needs careful differentiation between an optimized reaction step and realizing a commercially feasible process. We have also highlighted the role of 3D printing in fabricating prototype and scalable flow systems.

Assessing the impact of deviations in optimized multistep flow synthesis on the scale-up (vol 5, pg 838, 2020) - Sharma, M. K.; Raval, J.; Ahn, Gwang-Noh; Kim, Dong-Pyo; Kulkarni, A. A. (Reaction Chemistry & Engineering, 2021)